Garlic oil alleviates high triglyceride levels in alcohol‐exposed rats by inhibiting liver oxidative stress and regulating the intestinal barrier and intestinal flora. Issue 8 (29th March 2022) - Wang, Yanhui; Zhang, Huaqi; Teng, Xiangyun; Guo, Peiyu; Zuo, Yuwei; Zhao, Hui; Wang, Peng; Liang, Hui
Abstract: Garlic oil (GO) is a kind of natural extract extracted from garlic, which has strong antioxidant activity. This study elucidates the protective mechanism of GO against alcohol‐induced high triglyceride levels. Sixty male Sprague Dawley rats were assigned to five groups, including a control group (CON), a model group (MOD) treated with alcohol 56% v/v at 8 ml kg −1 day −1 for 2 weeks then 10 ml kg −1 day −1 for 8 weeks, a low‐dose GO group (GO‐L) given GO at 20 mg kg −1 day −1, a high‐dose GO group (GO‐H) given GO at 40 mg kg −1 day −1, and a positive group (POS) given diammonium glycyrrhizinate at 200 mg kg −1 day −1 . The results showed that GO could significantly reduce the serum and liver triglyceride levels caused by alcohol exposure ( p < .05). The GO‐H group significantly reduced MDA level, increased SOD and GSH‐Px levels in serum, liver, and colon ( p < .05), significantly increased the levels of Sirt1 and PGC‐1α proteins and reduced FoxO1 protein level in liver ( p < .05), and significantly increased the levels of ZO‐1 and Claudin1 proteins in the colon compared to the MOD group ( p < .05). The 16S rRNA sequencing showed that the intestinal flora of the GO‐H group was significantly changed compared with the MOD group. In summary, GO has the potential to improve high triglyceride levels in serum and liver induced by alcohol exposure, which may be related to the inhibition of oxidative stress regulation of Sirt1 and its downstream proteins, and to the restoration of the intestinal barrier and intestinal flora. Abstract : GO can alleviate the high triglyceride levels caused by alcohol exposure by regulating Sirt1 and its downstream proteins FoxO1 and PGC‐1α to regulate oxidative stress. GO can also repair the mechanical barrier of intestinal mucosa and regulate intestinal flora, which may be related to the reduction of high triglyceride levels in alcohol‐exposed rats.